(untitled) (Global Journal of Medical Research, 2023)
Background The COVID-19 pandemic in the first wave in India had a high case fatality rate Vaccination and other preventive measures were implemented soon after Our study was conducted with an aim to assess the effect of a single dose of COVID-19 vaccine on patient outcome and clinical profile of patients admitted with the disease in the second wave Methods A prospective observational study was carried out at three community hospitals in a suburban area of Pune during the second wave after prior informed consent of patients through a digital questionnaire to record clinical demographic and laboratory data